Profitability in Micro Manufacturing Enterprises in Dibrugarh District of Assam - Nomani, Rubab Fatema; Sen, Alok (Indian Journal of Finance, 2019)
Profitability analysis is an important component of financial analysis. Profitability is a yardstick of the overall financial health of a business concern, and a very useful guide for the management, owners, shareholders, and creditors. In this paper, an attempt was made to assess profitability of 115 micro manufacturing enterprises in the district of Dibrugarh in Assam with firm level data collected through field survey. The techniques of cost - volume - profit analysis and profitability ratios were employed in the study. The results indicated that majority of the firms operated above the break-even point. However, although the micro enterprises operated at safe margins and were able to break even, they were operating with very low profit margins. The category-wise analysis revealed that the worst performing sectors were agro based enterprises and weaving and textiles based enterprises, both in terms of break even analysis and profitability analysis. This led us to recommend that the government’s support measures must specifically target these two weakest sectors among micro enterprises, with emphasis on financial inclusion. Also, operational efficiency in all categories needs to be improved through more investment on training in management and administration and research & development in small-scale enterprises.